On the role of muscle relaxation and elasticity in the adaptation process of distance runners - Nurmekivi, A.; Lemberg, H.; Pääsuke, M. (New Studies in Athletics, 2016)
The ability to run fast is generally considered to be connected with maximal strength and accompanying muscle hypertrophy. However, there are other important factors involved in distance running and the excessive or incorrect development of strength can have a negative impact on performance, not least because the coordination required for efficient movement and energy conservation can be compromised. A better approach would link the preferred development of muscles and connective tissues together with the application of elastic energy and moderate muscle hypertrophy. Good muscle elasticity requires the rapid alternation of muscle contractions and relaxation. The aim of this article is to analyse the possibilities for developing muscle elasticity and connecting it with the skill of relaxation in the long-term training and adaption process of distance runners. The authors review the existing literature and make the case for coaches to focus on developing tiie skill of fast voluntary relaxation. Although adaptive shifts are largely genetically determined, it is possible to achieve remarkable changes via targeted training. Further research and wide spread application in training will lead to a better understanding and the development of relevant training techniques.